Confirmatory factor analysis and factorial invariance of the APGAR-family scale in older adults in Lima - Iparraguirre Yaurivilca, Noemi E. (2022)
Background: Family functioning is an important factor in mental health, particularly in vulnerable populations such as the elderly. Therefore, it is necessary to have valid, reliable, and equitable measurement instruments for its adequate use in psychological assessment and intervention.  Objective: To analyze the evidence of validity, reliability and equity of the Family Functionality Scale (APGAR) in a sample of Peruvian older adults. Methods: A total of 522 older adults, aged 60 to 93 years (M=70.81, SD=7.62), responded to the APGAR scale. Results: Adequate fit indices were found for a three-factor correlated model: x2/gl=1.61, CFI=.99, TLI=.98, SRMR=.05, and RMSEA=.04. A relationship was also found between the APGAR scores and the WHO-5 (r=.318), which is evidence of convergent validity. Likewise, evidence of reliability of the scores was found (>.80); finally, the scale is invariant with respect to sex CFI (∆CFI< .01) and RMSEA (∆RMSEA< .01) are lower .01. Conclusions: The APGAR test gathers evidence of validity, reliability and fairness for its correct use in Peruvian older adults.